The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s00464-013-2831-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous drainage of infected pancreatic necrosis

Abstract: BackgroundThe role of percutaneous drainage in the management of infected pancreatic necrosis remains controversial, and ultrasound-guided technique is rarely used for this indication. The purpose of this study was to evaluate the safety and efficacy of sonographically guided percutaneous catheter drainage for infected pancreatic necrosis.MethodsThe patient group consisted of 16 men and 2 women. The mean age of the patients was 47 years. The median computed tomography severity index of acute pancreatitis was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
2
25
0
1
Order By: Relevance
“…Percutaneous drainage in our series was successful for 33 % of the patients [ 3 ], similar to the success rate reported in a recent prospective study by van Santvoort et al [ 4 ] (35 %). We think the lower success rate for PCD in our series was mainly due to a few technical complications that occurred early in our experience with this technique, and this issue is thoroughly explained in our article.…”
supporting
confidence: 88%
“…Percutaneous drainage in our series was successful for 33 % of the patients [ 3 ], similar to the success rate reported in a recent prospective study by van Santvoort et al [ 4 ] (35 %). We think the lower success rate for PCD in our series was mainly due to a few technical complications that occurred early in our experience with this technique, and this issue is thoroughly explained in our article.…”
supporting
confidence: 88%
“…However, in some cases, indications for drainage such as infection or pressure effects to the surrounding organ may occur earlier, warranting early intervention. Feasibility of percutaneous drainage within 4 weeks has been reported 12 13 14 but study regarding the feasible timing of endoscopic drainage for pancreatic fluid collection (PFC) has been limited. The aim of this study was to evaluate feasibility and safety of early (< 4 weeks) endoscopic drainage for PFC.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous pigtail tube drainage became the first-line treatment for IPN because of simple operation, convenience, and small disturbance to the patient. However, it was reported that the success rate of percutaneous drainage therapy for IPN was only 33% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%